Venture capital 3 - Chemmanur, Thomas J. (Henry Stewart Talks, 2014)
Contingencies in venture capital (VC) contracting, The use and benefits of convertible securities, Risk allocation using convertible debt/debt with warrants, Calculating cash flow to the VC from using convertible debts